1992
DOI: 10.1093/bja/69.5.511
|View full text |Cite
|
Sign up to set email alerts
|

Onset and Recovery of Rocuronium (Org 9426) and Vecuronium Under Enflurane Anaesthesia

Abstract: We have studied the onset, duration of action and recovery index of twice the ED90 of rocuronium (Org 9426) (0.6 mg kg-1) and of vecuronium (0.08 mg kg-1) in patients during enflurane anaesthesia. Rocuronium had a significantly shorter mean onset time of 1.8 (SD 0.4) min, compared with vecuronium 3.4 (0.8) min. Clinical duration (time for the first twitch in the train-of-four to recover to 25% of control) was similar for both drugs (29 (10) min vs 31 (12) min). Spontaneous recovery times (TOF ratio 70%) did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 4 publications
2
17
0
Order By: Relevance
“…The faster onset of good and excellent tracheal intubation conditions we found with rocuronium compared to vecuronium in this study are in keeping with those reported in other studies [10][11][12][13].…”
Section: Discussionsupporting
confidence: 93%
“…The faster onset of good and excellent tracheal intubation conditions we found with rocuronium compared to vecuronium in this study are in keeping with those reported in other studies [10][11][12][13].…”
Section: Discussionsupporting
confidence: 93%
“…There were no significant differences between the groups. Rocuronium is an isotonic solution with a pH of 4.0 by adding acetic acid or sodium hydroxide [13,14]. The pH of rocuronium in this study was 3.9 ± 0.1.…”
Section: Discussionmentioning
confidence: 91%
“…Rocuronium bromide is a new aminosteroidal nondepolarizing competitive neuromuscular blocking agent that is structurally related to vecuronium and is characterized by rapid onset and intermediate duration of action [14,15]. Injection of rocuronium is accompanied by a severe burning pain that results in brisk flexion of the elbow and wrist, which has been observed after induction of anesthesia [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Mayer et al, 22 stated that satisfactory intubating conditions were found with vecuronium at 60 seconds and none of them were excellent.…”
Section: Discussionmentioning
confidence: 99%